Implementasi Media Flipbook Dalam Pembelajaran IPAS Materi Wujud Zat Dan Perubahanya di Kelas V Sekolah Dasar - Nuraliah, Siti; Nabila G, Zahwa; Gustiani, Tiara Iyus; Heryadi, Yadi (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
This study aims to examine the implementation of flipbook media as an innovative alternative in improving students' understanding of the material. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. Participants in the study were teachers and grade V students at SDN 2 Banjaririgasi. The results of the study show that the use of flipbooks is able to facilitate a more contextual, visual, and fun learning process. Flipbooks encourage students to be more active, understand the concept of changing the form of substances microscopically and macroscopically, and relate the material to everyday life. In addition, teachers find it helpful in conveying material that was previously difficult to explain only through static images or lecture methods. This media has proven to be in harmony with dual coding theory and constructivist approaches, while supporting the development of technology-based learning and the Independent Curriculum. In conclusion, flipbooks are an effective and innovative medium in learning social studies in elementary schools and have the potential to change conventional learning patterns to be more interactive and meaningful.